Not Just Asking Questions: Effects of Implicit and Explicit Conspiracy Information About Vaccines and Genetic Modification. Issue 14 (6th December 2019) - Lyons, Benjamin; Merola, Vittorio; Reifler, Jason
ABSTRACT: While conspiracy ideation has attracted overdue attention from social scientists in recent years, little work focuses on how different pro-conspiracy messages affect the take-up of conspiracy beliefs. In this study, we compare the effect of explicit and implicit conspiracy cues on the adoption of conspiracy beliefs. We also examine whether corrective information can undo conspiracy cues, and whether there are differences in the effectiveness of corrective information based on whether a respondent received an explicit or implicit conspiracy cue. We examine these questions using a real-world but low-salience conspiracy theory concerning Zika, GM mosquitoes, and vaccines. Using a preregistered experiment ( N = 1018: https://osf.io/hj2pw/ ), we find that both explicit and implicit conspiracy cues increase conspiracy beliefs, but in both cases corrections are generally effective. We also find reception of an explicit conspiracy cue and its correction is conditional on feelings toward the media and pharmaceutical companies. Finally, we find that examining open-ended conspiracy belief items reveals similar patterns, but with a few key differences. These findings have implications for how news media cover controversial public health issues going forward.